EFECTO DE LA GnRH EN EL PROCESO DEL RECONOCIMIENTO MATERNAL DE LA PREÑEZ SOBRE LA SUPERVIVENCIA EMBRIONARIA EN ALPACAS - Araínga R., Mariluz (2003)
The effect of GnRH administered around the time of maternal recognition of prenancy on the embryonic survival rate was studied. It was used 67 adult female alpacas sexually receptive to the male, and bearing a preovulatory follicle ≥7mm, detected by rectal ultrasonography. Animals were distributed in three groups: G0 (n=23) as control; G1 (n=22) received 6 µg GnRH on day 4 after ovulation; and G2 (n=22) received 4 µg GnRH on days 8 and 9 after ovulation. The ocurrence of ovulation was confirmed through the detection of a corpus luteum (CL) on day 5 after ovulation. Fertilization and gestation viab-ility were monitored by CL development, structural changes of the uterine horns and presence of the embryonic vesicle on days 12, 18, 25 and 30 after ovulation, using rectal ultrasonography. The female sexual receptivity to the male was simultaneously evaluated. The number of females that ovulate was 20, 22 and 21 in G0, G1, and G2 respectively, and was presumed that conception has occurred. However, on day 12, the embryo survival rate was 90.5% in G1, 75.0% in G0,and 76.2% in G2. These values were statistically different (p<0.05) on day 25 and 30 between G1 (76.2%) and G2 (42.9%). The follicle diameter in G2 showed a continuos decrease from day 0 to day 5 and 12 after ovulation (7.4, 7.3 and 6.3 mm, respectively). The CL size of females that maintained pregnancy showed an increase from day 5 to day 12 and 18 after ovulation, while those of females that had embryonic mortality showed a significant (p<0.01) decrease since day 12 onwards. There was an inverse relationship between the diameter of CL and follicle size with embryonic mortality. It is concluded that GnRH decreased the size of the dominant follicle and embryo survival rate when applied around the time of maternal recognition of pregnancy.